Development and growth of tomato seedlings under efect of Ascophyllum nodosum extract - Souza, Bruno Goulart de Azevedo; Pereira, Luiz Aurelio Freitas; Souza, João Vitor Goulart de Azevedo; Albuquerque, José Ricardo Tavares de; Sousa, Leonardo Vieira de; Barros Júnior, Aurélio Paes (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
In the production phase of tomato seedlings, the use of Ascophyllum nodosum seaweed extract can become an organic viable alternative in agriculture, as an alternative biofertilizer, stimulating through its compounds the vegetative growth of the cultures that receive effect of its application. Thus, the present research aimed to verify the growth and development of IPA 6 tomato seedlings under the effect of Ascophyllum nodosum extract. The experiment was carried out in a greenhouse at the Agricultural Science Center of the Federal Rural Semi-Arid University, Mossoró campus, Rio Grande do Norte, from June to July 2015. The experimental design was a completely randomized design with four treatments (0, 0.3, 0.6 and 0.9 mL L-1) of doses of foliar fertilizer based on seaweed Ascophyllum nodosum, with four replications and each plot represented by 12 plants of the IPA 6 tomato variety. The research evaluated the following characteristics: leaf number, seedling height, root length, stem diameter, total dry matter and seedling height/stem diameter ratio. Except for seedling height/stem diameter ratio, all evaluated characteristics obtained the highest results at the dose of 0.9 mL L-1 applied every 7 days. Thus, we can conclude that this dose provides a better quality of tomato seedlings, being the dose recommended for utilization.